The feasibility of implementing renewable energy systems by local municipalities for households and economic entities - Olufemi Michael Oladejo; Elvin Shava; Tigere Paidamoyo Muringa (Frontiers in Energy Research)
As the urgency to combat climate change, environmental degradation and energy security intensifies, nations globally are exploring sustainable energy alternatives to reduce dependence on fossil fuels. This growing concern has urged local governments to seek renewable energy solutions. Municipalities are in an advantageous position to implement these systems, as they are often at the forefront of service delivery and the government closest to the people. Local municipalities can benefit households and economic entities by implementing renewable energy systems. More so, renewable energy sources, such as solar, wind, and hydroelectric power, are often more cost-effective and efficient than traditional ones, particularly in rural or remote areas. This study adopts a qualitative research approach using face-to-face interviews guided by a semi-structured interview to explore the technical, economic, and environmental feasibility of supporting households and economic entities in implementing renewable energy Seven (7) stakeholders from South Africa’s renewable energy sector were selected for the interviews using purposive sampling. Data collected was recorded and later transcribed into Microsoft Word for thematic analysis. The results revealed that local municipalities must invest in renewable energy systems to support households and business entities in implementing renewable energy. In addition, the result also showed that local municipalities must leverage the resources within their jurisdictions, such as wind, land, organic waste from landfills, agriculture, and municipal sanitation systems, to achieve their RE target. The study’s conclusions suggest that local municipalities must develop policies for best renewable energy practices to achieve renewable energy autonomy to support households and business entities in South Africa.